2011
DOI: 10.1111/j.1469-8986.2011.01229.x
|View full text |Cite
|
Sign up to set email alerts
|

Age, sex and individual differences in punishment sensitivity: Factors influencing the feedback‐related negativity

Abstract: The anterior cingulate cortex (ACC) is central to evaluating performance outcomes and has been linked to individual differences in affective responses to feedback. We used electrophysiological source localization to examine the feedback-related negativity (FRN) and related ACC activity during a gambling task in relation to punishment and reward sensitivity among 16- to 17-year-old adolescents (n=20) and 18- to 29-year-old adults (n=30). The FRN was larger for monetary loss compared to win feedback and larger f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
95
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 65 publications
14
95
1
1
Order By: Relevance
“…As yet, there is little consistent evidence as to whether the FRN is substantially different in adolescent boys compared to girls. Yi et al [29] reported that males had larger (more negative) FRNs than females in feedback on a gambling task, whereas Santesso et al [26], using a similar task, reported the opposite finding. However, neither of these two studies found age differences in the FRN in comparison to their adult group, nor did they find any sex-by-age interactions.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…As yet, there is little consistent evidence as to whether the FRN is substantially different in adolescent boys compared to girls. Yi et al [29] reported that males had larger (more negative) FRNs than females in feedback on a gambling task, whereas Santesso et al [26], using a similar task, reported the opposite finding. However, neither of these two studies found age differences in the FRN in comparison to their adult group, nor did they find any sex-by-age interactions.…”
Section: Introductionmentioning
confidence: 76%
“…The EEG was rereferenced using averaged mastoids, and data were divided into 1,200-ms epoch beginning 200 ms before the feedback. The epochs were filtered (1-30 Hz) [for a similar approach, see [26,28,30]] and baseline corrected using the 200-ms prefeedback interval. Any sweep in which the ERP amplitude exceeded ±50 µV was discarded from further analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From research on individuals with depression (Tucker, Luu, Frishkoff, Quiring, & Poulsen, 2003) and healthy individuals with selfreported feedback sensitivity ratings Santesso et al, 2011), it is evident that the amplitude of the FRN differs between individuals in general (see van Noordt & Segalowitz, 2012, for a review). Accordingly, toddlers who show a smaller differential brain response to feedback on their actions might be, in general, less sensitive to feedback rather than reflecting a relatively immature feedback processing system.…”
Section: Functionality Of the Developing Feedback Processing Systemmentioning
confidence: 99%
“…2. Some toddlers who show weaker signals might just be less sensitive to feedback in general [5]. For these toddlers, socks have to be very, very different in order for them to see that they do not match.…”
Section: Brain Signalsmentioning
confidence: 99%